2008
DOI: 10.1111/j.1526-4610.2007.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine‐N‐Methyl Transferase Polymorphism and Risk for Migraine

Abstract: The results of the present study suggest that HNMT polymorphism in not related with the risk for migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…Recruitment of patients was done in the general neurological clinics of 3 University Hospitals during the period between September 2006 and August 2007 (the onset of migraine attacks was under age 15 years in 113 patients, positive family history for migraine was reported by 147 patients, and 98 of them had MWA). Most of these patients have participated previously in other genetic association studies reported by our group …”
Section: Methodsmentioning
confidence: 99%
“…Recruitment of patients was done in the general neurological clinics of 3 University Hospitals during the period between September 2006 and August 2007 (the onset of migraine attacks was under age 15 years in 113 patients, positive family history for migraine was reported by 147 patients, and 98 of them had MWA). Most of these patients have participated previously in other genetic association studies reported by our group …”
Section: Methodsmentioning
confidence: 99%
“…All eligible patients were invited to participate and all of them agreed to do so. These patients participated in other genetic association studies by our group …”
Section: Methodsmentioning
confidence: 99%
“…In the realm of genetics and migraine, it was hypothesized that an association between migraine and polymorphisms of the gene encoding histamine N‐methyltransferase, the enzyme which degrades histamine in the CNS, might exist. However, a recent study has failed to demonstrate this 208 …”
Section: Histamine and Headachementioning
confidence: 99%